Human IgG responses to the Aedes albopictus 34k2 salivary protein: analyses in Réunion Island and Bolivia confirm its suitability as marker of host exposure to the tiger mosquito - Buezo Montero, Sara; Gabrieli, Paolo; Poinsignon, Anne; Zamble, Bi Zamble Hubert; Lombardo, Fabrizio; Remoue, Franck; Arcà, Bruno (Parasites & vectors, 2022)
The rapid worldwide spreading of Aedes aegypti and Aedes albopictus is expanding the risk of arboviral diseases transmission, pointing out the urgent need to improve monitoring and control of mosquito vector populations. Assessment of human-vector contact, currently estimated by classical entomological methods, is crucial to guide planning and implementation of control measures and evaluate transmission risk. Antibody responses to mosquito genus-specific salivary proteins are emerging as a convenient complementary tool for assessing host exposure to vectors. We previously showed that IgG responses to the Ae. albopictus 34k2 salivary protein (al34k2) allow detection of seasonal and geographic variation of human exposure to the tiger mosquito in two temperate areas of Northeast Italy. The main aim of this study was to confirm and extend these promising findings to tropical areas with ongoing arboviral transmission. IgG responses to al34k2 and to the Ae. aegypti orthologous protein ae34k2 were measured by ELISA in cohorts of subjects only exposed to Ae. albopictus (Réunion Island), only exposed to Ae. aegypti (Bolivia) or unexposed to both these vectors (North of France). Anti-al34k2 IgG levels were significantly higher in sera of individuals from Réunion Island than in unexposed controls, indicating that al34k2 may be a convenient and reliable proxy for whole saliva or salivary gland extracts as an indicator of human exposure to Ae. albopictus. Bolivian subjects, exposed to bites of Ae. aegypti, carried in their sera IgG recognizing the Ae. albopictus al34k2 protein, suggesting that this salivary antigen can also detect, even though with low sensitivity, human exposure to Ae. aegypti. On the contrary, due to the high background observed in unexposed controls, the recombinant ae34k2 appeared not suitable for the evaluation of human exposure to Aedes mosquitoes. Overall, this study confirmed the suitability of anti-al34k2 IgG responses as a specific biomarker of human exposure to Ae. albopictus and, to a certain extent, to Ae. aegypti. Immunoassays based on al34k2 are expected to be especially effective in areas where Ae. albopictus is the main arboviral vector but may also be useful in areas where Ae. albopictus and Ae. aegypti coexist.